The Integrated Development Strategy of Coastal Industrial Areas and City Based on Underground Space Development. (27th August 2021) - Shao, Feng; Shi, Pingyang; Ding, Yusheng; Dong, Ce
Abstract : As a crucial node of Qingdao's construction of a modern international metropolis, a topnotch marine port, a demonstration zone for local economic and trade cooperation of the Shanghai Cooperation Organization (SCO), and an international shipping trade financial innovation center, the Qingdao Cruise Port warrants transformation to adapt to the future development of Qingdao city. Besides, with the constant increase in the intensity of urban underground space (UUS) development in Qingdao, the organic integration of underground space reconstruction and urban development in the cruise port area must be accentuated. Taking the underground space development project in Qingdao Cruise Port as the background, this study analyzes the multidimensional development and utilization of underground space in the project (the functional distribution of the two-dimensional plane and the stereo integration of the three-dimensional space). In addition, this study explores strategies to promote the organic integration of industrial areas and cities through underground space development. Expanding the research field of UUS, this study provides reference cases for the transformation of old industrial areas in other coastal cities.